STRATEGIC HUMAN RESOURCE MANAGEMAENT POLICY OF DEPARTMENT OF LEARNING ENCOURAGEMENT, MINISTRY OF EDUCATION - Chanchai, Sudaratch; Udomwisawakul, Noppadol; Rajphaetyakhom, Chamnian (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The purposes of this research were to (1) study the situation of the strategic human resource management policy of Department of Learning Encouragement, Ministry of Education (2) study relationship between strategic human resource management and the success of strategic human resource management policy of Department of Learning Encouragement, Ministry of Education, and (3) propose guidelines for developing strategic human resource management policies of Department of Learning Encouragement, Ministry of Education. The research approaches adopted in this study were mixed methods. In the quantitative research, the population was civil servants, government employees and temporary employees of Department of Learning Encouragement based in the central offices, totaling 432 people. The sample size was 208 people and the study instrument was a questionnaire. Data analysis was carried out by using statistical tools, namely frequency, percentage, mean, standard deviation, and analysis by Pearson’s correlation coefficient. In the qualitative research, the population was 12 executives of the directorial level based in the central offices. The sample group of three was the executives of the directorial level directly supervising the human resource development. The purposive sampling was employed to select those directly involved with the issues studied. The study instruments were structured interviews. The results of the study revealed that (1) the situation of the strategic human resource management policy of Department of Learning Encouragement, Ministry of Education, concerning the overall factors in strategic human resource management in four areas were in a high level while the implementation of the aforementioned policy still encountered some restrictions, namely the work analysis and the current human resource position planning were not in line with the current mission of Department of Learning Encouragement; human resource development and training plans were not diverse and up-to-date; and the policy promotion to incentivize the capable personnel was still lacking (2) strategic human resource management factors had a positive relationship with the success of the strategic human resource management policy of Department of Learning Encouragement, Ministry of Education, with a statistical significance at 0.01, and (3) development guidelines were that recruitment and selection of human resources had the least relationship with the success of the strategic human resource management policy. As such, resource allocation in personnel should be made more sufficient, suitable for and in line with the mission; the personnel should be encouraged to undergo regular trainings; clear and suitable career paths of the personnel should be promoted and supported; and those with good virtues, high capabilities and potentials should be promoted to raise the personnel’s motivation and morale.